Long-Term Influence of Incidental Emotions on the Emotional Judgment of Neutral Faces - Nudelman, Marta F.; Portugal, Liana C. L.; Mocaiber, Izabela; David, Isabel A.; Rodolpho, Beatriz S.; Pereira, Mirtes G.; Oliveira, Leticia de (Frontiers in Psychology, 2022)
Background: Evidence indicates that facial stimuli may be subject to influences from incidental factors, and these influences are particularly powerful when facial expressions are ambiguous such as neutral faces. However, little research has investigated whether emotional contextual information presented during a preceding and unrelated experiment could be pervasively carried over from this experiment to another experiment to modulate neutral face processing. Objective: The present study aims to investigate whether an emotional text presented in a first experiment could generate negative emotion towards neutral faces in a second experiment unrelated to the previous one. Methods: Ninety-nine students (all women) were randomly assigned to read and evaluate a negative text (negative context) or a neutral text (neutral text) in a first experiment. In a subsequent second experiment, participants performed two tasks: 1) an attentional task in which neutral faces were presented as distractors and 2) a task of emotional judgement of neutral faces. Results: The results show that in the negative context, participants rated more faces as negative than in the neutral context. No significant result was found for the attentional task. Conclusion: Our study demonstrates that incidental emotional information available in a previous experiment can increase participants' propensity to interpret neutral faces as more negative when emotional information is directly evaluated. Therefore, the present study adds important evidence to the literature that our behaviour and actions are modulated by previous information in an incidental or low perceived way similar to what occurs in everyday life, modulating our judgements and emotions.